A New Start Method of Wireless Parallel Auxiliary Inverter - Erlin YANG; Kan DONG; Yingtao MA (机车电传动)
In the practical application of high-speed EMUs and urban rail vehicle, the grid-connection of multiple auxiliary inverters is a key technical problem, which mainly involves the starting logic and the timing sequence of the train control system, and the starting method of the auxiliary inverter. In order to solve the problem of the startup conflict of several auxiliary inverters in the current engineering application, shorten the startup time of auxiliary system and reduce the train control difficulty of auxiliary inverter, a new startup method of auxiliary inverter was proposed. Through reasonable design of start-up logic and optimal control strategy, the deficiencies of traditional auxiliary converter control methods were improved. Finally, the experimental validation was completed, which proved that the new start method was effective and feasible.